MEMAHAMIMANAJEMENPRIVASIKOMUNIKASIINDIVIDUSAAT MELAKUKANLIVESTREAMINGDIMEDIASOSIALTIKTOK - Mumtaz, Tsaniyatul; Manalu, S. Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research examines how individuals manage privacy while live streaming on TikTok using a qualitative approach through Interpretative Phenomenological Analysis (IPA). By conducting in-depth interviews with individuals actively engaged in TikTok live streaming, the study reveals various perspectives on privacy, where personal information and family issues are considered highly sensitive, while topics such as complaints, work-related problems, education, and romantic relationships are easier to share. The participants employ various strategies for privacy management, such as utilizing TikTok's privacy features and setting boundaries during the broadcast. Supporting Communication Privacy Management (CPM) theory, the findings highlight the dynamic nature of privacy management, influenced by factors such as gender, motivation, and audience interaction, providing valuable insights into the complexities of digital privacy in the context of social media